2017
DOI: 10.1089/thy.2016.0336
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Nodule Size at Ultrasound as a Predictor of Malignancy and Final Pathologic Size

Abstract: Thyroid nodule size is inversely related to malignancy risk, as larger nodules have lower malignancy rates. However, the relationship of size to malignancy varies by FNA status. All nodules (regardless of FNA status) demonstrate a risk trough at ≥2 cm. Nodules subject to FNA show step-wise decline in malignancy rates by size, demonstrating that size alone should not be considered as an independent risk factor. Size at ultrasound shows relatively good correlation with final pathologic size. False negative rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
74
4
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 37 publications
13
74
4
11
Order By: Relevance
“…We learned from the results that with the increase in the thyroid nodular size from 0.3 to 2 cm, the sensitivity of the UGSR to diagnose PTCs decreased while the specificity increased. The results of subgroup analysis may be because smaller nodules had higher malignancy rates than larger nodules in the PTC group . Therefore, the predictive value of the hypoechogenicity for malignancy decreased with increasing size.…”
Section: Discussionmentioning
confidence: 98%
“…We learned from the results that with the increase in the thyroid nodular size from 0.3 to 2 cm, the sensitivity of the UGSR to diagnose PTCs decreased while the specificity increased. The results of subgroup analysis may be because smaller nodules had higher malignancy rates than larger nodules in the PTC group . Therefore, the predictive value of the hypoechogenicity for malignancy decreased with increasing size.…”
Section: Discussionmentioning
confidence: 98%
“…The accumulated data presented in Table shows that the majority of malignant tumors with false negative FNA results in large thyroid nodules were FTC (32.3%) and follicular variant PTC (53.8%). The prevalence of FTC was higher among large nodules and the proportion of FTC was higher among large malignant thyroid tumors . A recent study has reported that follicular variant PTC with false negative FNA results was exclusively found in encapsulated follicular variant PTC, and the size of follicular variant PTC with false negative FNA results was larger than that of follicular variant PTC without false negative FNA results .…”
Section: Discussionmentioning
confidence: 91%
“…There have been many conflicting reports in terms of false negative rate and nodule size in overall thyroid nodules . Although the reason for the conflicting results among the studies is not clear, it may be related to the proportion of FTC among malignant tumors and the size distribution of PTC in the study population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Cavallo et al also investigated the association between nodule size and malignancy; they reported that malignancy risk was inversely correlated with nodule size, with smaller nodules having higher malignancy rates. Ultrasound and elastography both showed higher sensitivity for nodules larger than 10 mm and higher specificity for nodules smaller than 10 mm .…”
Section: Discussionmentioning
confidence: 99%